Le rite est dé-corps - Maertens, Jean-Thierry (Anthropologica, 2022)
The body is simultaneously physical toil and erogenous, production or reproduction on the one hand, yearning for a lost origin on the other. Rituality is a cultural undertaking which attempts to transform this erogeneous element into a "signifier," to transpose this semiotic reality on a symbolic level. Thus the body is reduced to a "sense." Rituality becomes disembodiment, not only by its synchronic reduction of the body but, even moreso, by its "diachronism" progressively focalizing surfaces increasingly distant from the body.